NEXUS ENDOWMENT FUND POLICY IN EDUCATION SECTOR AND GRAND DESIGN POLICY OF INDONESIAN NATIONAL TALENT MANAGEMENT - Putra, Fahdiansyah; Nurdin, Nurliah; Utomo, Tri Widodo Wahyu; Saksono, R. N. Afsdy (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
A deep understanding of the close relationship between the Endowment Fund Policy in Education and the Grand Design Policy of National Talent Management in Indonesia is analyzed in this article through the perspective of policy coherence. By applying the nexus approach, this study aims to understand how these two interconnected policies can synergize optimally to advance human resource (HR) development at the national level. Qualitative analysis of policy documents and related literature indicates the potential for significant relationships, where endowments can act as a stable long-term funding source for various talent development initiatives. However, to achieve maximum synergy, effective coordination and integration between various stakeholders and institutions are absolute prerequisites. This article will also highlight the various opportunities and challenges faced in efforts to realize policy coherence in order to achieve sustainable and globally competitive HR development.